26 Combined hormonal contraceptive use is not protective against musculoskeletal conditions or injuries: A systematic review with data from 5-million women. (25th January 2023) - Losciale, Justin M; White, Lynita; Squier, Kipling; Beck, Charlotte; Guy, Sarah; Scott, Alex; Prior, Jerilynn C; Whittaker, Jackie
Abstract : Introduction: Half of young women start combined hormonal contraceptive (CHC) use for non-contraceptive reasons including 'controlling' their menstrual cycle to prevent injuries. These decisions should be evidence-based. This study assessed the association between CHC use and musculoskeletal tissue pathophysiology, injuries, or conditions. Materials and Methods: After protocol registration, five databases were searched to 04–2022. Intervention and cohort studies assessing the association between new or ongoing use of CHC and musculoskeletal tissue pathophysiology, injury, or condition outcome in post-pubertal women were included. Record screening, data extraction, and risk-of-bias assessment were duplicated (blinded). Meta-analyses were not possible. Semi-quantitative syntheses followed a modified GRADE approach. Results: Across 50 included studies, we assessed the effect of CHC use on 30 unique outcomes (75% bone-related). Serious risk-of-bias was judged present in 82% of studies, with 52% adequately adjusting for confounding. Meta-analyses were not possible due to heterogeneity in outcome methods, estimate statistics, and comparison conditions. Based on semi-quantitative synthesis, there is low certainty evidence that CHC use is associated with higher future fracture risk (RR 1.02–1.20), and total knee arthroplasty (RR 1.00–1.36). There is very low certainty evidence of unclear relationships between CHC use and a wide range of bone health outcomes. Evidence about the effect of CHC use on musculoskeletal tissues beyond bone, and the influence of use in adolescence versus adulthood is limited. Conclusion: Given a paucity of high-certainty evidence that CHC use is protective against musculoskeletal pathophysiology, injury, or conditions, it is premature and inappropriate to prescribe CHC for these purposes.